Management of Fisheries and Marine Resources in Improving the Welfare and Empowerment of Coastal Communities (A Case Study at Desa Seri Kec. Nusaniwe Ambon City) - Soselisa, Hobarth Williams (Sangia Research Media and Publishing, 2021)
The author argues yhat management of fisheries and marine resources to day is more on ecological and economic goals than indirect use value, while direct use value is often used regardless of is sustainability. So far, direct benefits for improving the welfare of coastal communitiies have only been limited to a local scale with limited equipment. This condition is the responsibility of all parties, including policy makers, in increasing the economic value of fisheries and marine resources. This type of research is descriptive qualitative. Obervation data collection methods, indepth interviews, FGD and documentation studies. Data were collected from informants, government (Camat, Raja Nusaniwe), people who carry aut activities to maintain and preserve coastal and marine ecosystems that are in critical condition such as coral reefs, seagrass beds, estuaries and mangrove forests. The economic value of fisheries and marine resources can be increased by managing them sustainably. To increase the useful value of these resources, various efforts are made with the right methods, so that the management of fisheries and marine resources can be optimized for the welfare of coastal communities.The result of this study indicate that the result of fisheries and marine resourece management efforts are still felt by people who are far from coastal areas. Meaning that entrepreneurs and middlemen who have tasted the results of fishery and marine resources have been strived for by coastal communities. That efforts to improve the welfare of the peisir people also depend on the management of fisheries and marine resources, which means that if fisheries and marine resources are not conserved, there will be massive exploitation by foreign ships and fish companies that are only looking for profit.